IMPLEMENTASI JASA PELAYARAN YANG DAPAT DITAWARKAN OLEH PEMERINTAH INDONESIA DI SELAT MALAKA MENURUT HUKUM INTERNASIONAL - Bakhunizar, Mohamad Megi Mif; Lestari, Maria Maya; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
This writing discusses how the shipping services offered by Indonesia in order to compete with ports in the world, especially in the Malacca Strait, because basically Indonesia has more potential to take advantage of the Malacca Strait which is currently still unable to maximize because there are many obstacles faced. This is the point of the problem where even though most of the Malacca Strait is in the territory of Indonesia, in this case the author examines what obstacles occur.In this case, the writer uses a normative research type, which is a descriptive type of research that describes actual events. The data analysis used by the researcher is qualitative data analysis, namely the analysis which does not use statistics or other things. However, researchers simply describe descriptively from the data obtained.The results of this study can be concluded into three main things. First, the existing shipping service offered by the Indonesian government in the Malacca Strait, namely the Shipping Guidance Service. The two services that have been offered by countries are several, namely taking from Singapore and Malaysia including parking services, crane services, and loading and unloading facilities between ships. The three services that Indonesia can offer in the future include parking services, fuel supply services, storage services and ship waste management.Keywords : IMO, Shipping Service, Scout Service, Malacca Strait, Indonesia.